Analisis Faktor-faktor Kontaminasi Escherichia coli O157:H7 pada Sumber Air Peternakan Sapi Perah Rakyat di Kabupaten Sleman = The Analysis of Escherichia coli O157:H7 Contamination - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
A study on the contamination of Escherichia coli {E.coli) O157:H7 in water source of dairy cow farm had been conducted over 108 samples in smallholder dairy cows in the District of Sleman. Determination of sample amount in each village was taken proportionally and samples were taken by simple random. The objective study was to investigate E. coli O157:H7 contamination in water source of dairy cow farm and risk factors used in. The Contamination in the water was found by some treatment using SMAC selective media. The negative coloni in SMAC would be colorless-suspected as E.coli O157:H7. Furthermore it was tested by using commercial anti-serum kit O157:H7. The results showed that the prevalence of E.coli O157:H7 contamination in the water in smallholder dairy cow in the District of Sleman was 9.26 %. The result of the predictive model building of E.coli O157:H7 in water of dairy cows identified two risk factors, namely experience of the farmer (P = 0.0154